2022
DOI: 10.4049/jimmunol.2200346
|View full text |Cite
|
Sign up to set email alerts
|

Ring Finger Protein 215 Negatively Regulates Type I IFN Production via Blocking NF-κB p65 Activation

Abstract: Germline-encoded pattern recognition receptors (PRRs) recognize molecules frequently found in pathogens (pathogen-associated molecular patterns [PAMPs]) during viral infection. This process induces production of IFNs, leading to expression of IFN-stimulated genes to establish a cellular antiviral state against viral infection. However, aberrant activation of the IFN system may cause immunopathological damage and systemic autoimmune diseases such as systemic lupus erythematosus. Stringent control of IFN signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Although RNF215 showed the highest induction in LNCaP cells, it was not chosen as candidate gene because of the general lack on study data. RNF215 expression is only reported to be upregulated by viral infection in human macrophages and might play an important role in the pathogenesis of autoimmune diseases ( 30 ). In addition, RNF215 is introduced within a four−gene methylation signature to predict the survival outcome of head and neck squamous cell carcinoma ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although RNF215 showed the highest induction in LNCaP cells, it was not chosen as candidate gene because of the general lack on study data. RNF215 expression is only reported to be upregulated by viral infection in human macrophages and might play an important role in the pathogenesis of autoimmune diseases ( 30 ). In addition, RNF215 is introduced within a four−gene methylation signature to predict the survival outcome of head and neck squamous cell carcinoma ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, to the best of the authors' knowledge, only a few studies of the RNF215 protein have been performed. Wu et al (17) indicated that RNF215 can bind to the NF-kB p65 subunit by partially inhibiting type I interferon (IFN) production and limiting the accumulation of NF-kB in the promoter region of IFNB1. Ma et al (18) suggested that high RNF215 expression was associated with poor overall survival (OS) of head/neck squamous cell carcinoma.…”
Section: Association Of Kras Nras Braf and Pik3ca Gene Mutations With...mentioning
confidence: 99%
“…To date, only a few studies have been conducted on the RNF215 protein. Wu et al (8) reported that RNF215 interacts with p65 to reduce the production of type I interferons (IFNs); thus, it is considered to be a key negative regulator of type I IFNs and has been considered a potential target for disease intervention with aberrant IFN production. Ma et al (9) suggested that high RNF215 expression is associated with poor overall survival (OS), demonstrating its function as a head and neck cancer (HNSC) oncogene.…”
Section: Introductionmentioning
confidence: 99%